Cascading Effects Within Soil Food Web Amplify Fungal Biomass and Necromass Production - Shixiu Zhang; Yakov Kuzyakov; Zhongjun Jia; Edith Bai; Elly Morriën; Aizhen Liang (Global Change Biology, 2025)
Soil food webs regulate microbial biomass and necromass production and are therefore critical for carbon sequestration. The mechanisms by which top predators regulate microbial necromass formation across multitrophic levels in the real‐world soil food web remain nearly unknown. This study investigates how top‐down forces—from omnivorous‐predaceous nematodes to microbivorous nematodes and microbes—affect the formation of microbial necromass within tritrophic food webs under contrasting tillage regimes (tillage (till) vs. no‐tillage (no‐till)) on black soils (Mollisols), using a 1‐year 13 C‐labeled straw in situ tracing experiment integrated with a long‐term (> 5 years) tillage trial. The fungal‐to‐bacterial necromass ratio increased strongly in the no‐till soil compared to the till soil, with omnivores‐predators being the key factor for these changes. In the no‐till soil, abundant and diverse omnivores‐predators (46% and 67% higher in abundance and richness than in the till soil) created a typical predator–prey relationship with fungivores. This relationship was characterized by heavy predation on fungivores (51% of omnivore‐predator diet) and opposite 1‐year dynamics of 13 C content between omnivores‐predators and fungivores. Such a predator–prey relationship substantially reduced fungivore activity (73% and 90% decrease in 13 C content and enrichment rate), while accompanied by increased fungal activity (64% and 50% increase in 13 C content and enrichment rate) in the no‐till soil compared to the till soil. This predator‐driven cascade down the food chain amplified the fungal contribution to the fungal‐to‐bacterial necromass ratio. Conversely, these interactions, disrupted by continuous tillage, weakened fungal functions by interrupting the trophic cascade. In conclusion, these tiny yet ubiquitous omnivorous‐predaceous nematodes exert a disproportionate impact on necromass formation by boosting fungal biomass and activity. Further manipulative experiments targeting multi‐trophic interactions are essential to disentangle the mechanisms of microbial necromass formation, given the inherent complexity of soil food webs and the observational nature of this study.